2022
DOI: 10.1159/000522662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rapid On-Site Evaluation on Diagnostic Accuracy of Thyroid Fine-Needle Aspiration

Abstract: <b><i>Introduction:</i></b> Fine-needle aspiration (FNA) is well-established for the evaluation of suspicious thyroid nodules. However, a significant proportion is nondiagnostic. Rapid on-site evaluation (ROSE) has been proposed to improve the overall adequacy of FNA. <b><i>Methods:</i></b> Retrospective cohort study comparing adequacy of thyroid FNA findings pre- and postimplementation of ROSE at a tertiary center in Switzerland. Patients undergoing thyroid FNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The authors concluded that ROSE with a Bethesda categorization significantly increased diagnostic accuracy at both qualitative and quantitative levels, resulting a standard of care for thyroid FNA. Similarly, in a study by Fawcett et al [ 23 ] of 309 FNAs and 101 cases with ROSE, implementation of ROSE decreased the nondiagnostic cases from 41.1% to 23.8%. Procedures performed with ROSE also decreased repeated FNAs from 29.1% to 20.8%, even reducing the number of FNAs per nodule from 1.4 to 1.2 ( p = 0.04).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The authors concluded that ROSE with a Bethesda categorization significantly increased diagnostic accuracy at both qualitative and quantitative levels, resulting a standard of care for thyroid FNA. Similarly, in a study by Fawcett et al [ 23 ] of 309 FNAs and 101 cases with ROSE, implementation of ROSE decreased the nondiagnostic cases from 41.1% to 23.8%. Procedures performed with ROSE also decreased repeated FNAs from 29.1% to 20.8%, even reducing the number of FNAs per nodule from 1.4 to 1.2 ( p = 0.04).…”
Section: Discussionmentioning
confidence: 78%
“…ROSE is a widely used and effective diagnostic procedure during a needle aspiration biopsy of different organs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In the field of thoracic pathologies, several studies have demonstrated the utility of ROSE during both transbronchial and percutaneous needle aspiration techniques [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fine needle aspiration cytology (FNAC) is a rapid, safe, minimally invasive and highly accurate diagnostic tool for evaluating benign and malignant conditions 1–8 in various superficial and deep‐seated organs, including lymph nodes 9–12 . The incorporation of rapid on‐site evaluation (ROSE) further enhances its utility by gauging sample adequacy, leading to a notable decrease of approximately 20% in inadequate rates 4,13 . The precision of FNAC's diagnostic outcomes is augmented through immunocytochemistry (ICC) on diverse substrates such as cell block (CB), liquid‐based cytology (LBC) or smears, along with molecular testing, 14–17 and flow cytometry (FC) for lymphoproliferative processes 6,10,18–24 …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, despite the documented high sensitivity and specificity values, 2,4,25 FNAC may prove insufficient to reach actionable diagnoses in certain pathologies, particularly those necessitating extensive immunohistochemical panels and molecular testing, or intricate cases wherein histological architectural features are pivotal for diagnosis 5,20 . Core needle biopsy (CNB) emerges as a potent sampling technique offering the advantage of revealing tissue architecture and obtaining samples more substantial than those garnered via FNAC and CB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation